Do ponto de vista da caserna: memórias do cotidiano e experiências de militares da aeronáutica em Belém durante o regime militar (1964-1985) - SANTOS, Carlos Eduardo dos Santos e (Universidade Federal do Pará, 2014)
This work discusses the perceptions of the population of Belém on the period of the military regime of 1964, focusing on the military segment: Graduates of Military Aeronautics. We seek to understand the experience of everyday life in the state capital in the period 1964-1985. It manifests itself beyond politics and economics, depicting aspects of the company relating to work, leisure and private life, in which the different situations and instances are experienced and acquire different meanings and senses in the day-to-day. We aim to understand the meanings attributed by the military to their daily activities, whether at the institutional level or in the middle calendar. We use this insight to the documentation (photographic records, newsletters, posters) of the First Regional Air Command headquartered in Belém (I COMAR), and systematic interviews of military personnel and their families. These two spheres - Civil-Military - are focused on crossing their experiences in the civil, may have a direct or indirect relation with the political, economic and social aspects of the military regime.